2019
DOI: 10.1016/j.diabres.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes education and self-management on the quality of care for people with type 1 diabetes mellitus in the Middle East (the International Diabetes Mellitus Practices Study, IDMPS)

Abstract: These relationships between diabetes education, self-management and glycemic control suggest that diabetes education provides knowledge and skills to optimize self-management, favoring HbA target attainment. Middle East health authorities should search for ways to facilitate access to diabetes education to optimize treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
6
21
1
4
Order By: Relevance
“…In summary, these findings from Waves 1-4 in Latin America, and those reported previously from the IDMPS study for other waves and regions, have proved the strong relationships between diabetes education, self-management and attainment of HbA1c target [11,22]. Our results suggest that health authorities, policymakers, insurers, healthcare administrators and providers should increase efforts to ensure widespread healthcare coverage and access to education about diabetes self-management in order to decrease the heavy burden of T1DM for patients, the healthcare budget and society overall.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In summary, these findings from Waves 1-4 in Latin America, and those reported previously from the IDMPS study for other waves and regions, have proved the strong relationships between diabetes education, self-management and attainment of HbA1c target [11,22]. Our results suggest that health authorities, policymakers, insurers, healthcare administrators and providers should increase efforts to ensure widespread healthcare coverage and access to education about diabetes self-management in order to decrease the heavy burden of T1DM for patients, the healthcare budget and society overall.…”
Section: Discussionsupporting
confidence: 79%
“…Supporting these recommendations, our data showed that participants who had received diabetes education were more likely to practice self-management and to attain HbA1c values < 7% (53 mmol/mol), than those without education. In the Middle East population of IDMPS, self-management was a significant independent predictor of glycemic control [22]. This was not the case in the current study, though glucometer availability was a predictor of glycemic control, and this was also strongly linked with self-monitoring of blood glucose: 98% of patients who owned a glucometer practiced SMBG compared with 1% of those without a glucometer.…”
Section: Discussioncontrasting
confidence: 67%
“…11 DM self-management education (DSME) and support is a crucial part of establishing and implementing the principles of diabetes care. 10 Many reviews were conducted to evaluate the benefits of DSME programs for T2DM patients in developed 12,13 and developing countries; 14 however, only one review study was conducted specifically to assess the benefits of such programs for patients living in ME countries and was focusing on T1DM patients 15 while no review study was conducted on T2DM patients. Therefore, this study aimed to review the effectiveness and factors affecting the success of DSME programs in T2DM patients living in ME countries.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of knowledge could explain their low adequacy of self-care as revealed in the study results. In congruence with this, a study in Dubai found a significant close relationship between the knowledge of diabetic children and their self-care practices (José Gagliardino et al, 2018) [16] . The implementation of the present study training program was associated with significant improvements in diabetic schoolchildren's knowledge of diabetes and related self-care practices.…”
Section: Discussionmentioning
confidence: 76%